Strigolactone perception and deactivation by a hydrolase receptor DWARF14 - Yoshiya Seto (Nature Portfolio, 2019)
Cleavage of strigolactone by the D14 receptor was assumed to produce an active intermediate that promotes signaling. Here the authors show that D14 activity is not dependent on cleavage activity and propose a new model whereby ligand hydrolysis serves to deactivate strigolactone signaling.